The penal voluntary sector: a hybrid sociology - Tomczak, Philippa (The British journal of criminology, 2019)
The penal voluntary sector (PVS) is an important, complex, under-theorized area. Its non-profit, non-statutory organizations are highly significant in the operation of punishment around the world, yet ill understood. Burgeoning scholarship has begun to examine specific parts of the sector, particularly individualized service delivery. We offer a five-paradigm framework that more fully conceptualizes the PVS, including different types of service delivery and important campaigning work. Our hybrid framework applies and extends influential four-paradigm model of social theory given by Burrell and Morgan (Burrell, G. and Morgan, G. (1979), Sociological Paradigms and Organisational Analysis: Elements of the Sociology of Corporate Life. Routledge), which maps the theoretical diversity underpinning varying organizational activities. Our framework (1) provides ideal types, which illustrate the range, fluidity and hybridity of PVS programmes and practices and (2) highlights the (potential) roles of brokers in (re)directing activity.